The ransposition of the musculoaponeurtotic system of the tensor fascia lata in the repair of the anterolateral abdominal wall in its lower sector, conditioned by the excision of desmoid tumors - Varela Soto, Ruben M (Cirugía del Uruguay, 2020)
Presented at session 14th August 1963